Autumn migration of some passerines on the island of Capri, southwestern Italy - Waldenström, Jonas; Hjort, Christian; Andersson, Arne (Ornis Svecica, 2006)
This paper presents and analyses autumn migration data on phenology and biometrics for 12 species of birds trapped at the Capri Bird Observatory, south-western Italy. The material has been collected over 15 years, mainly in two periods, 1959—1963 and 1994—2004. The passage of trans-Saharan migrants (like the Garden Warbler Sylvia borin) peaks in late September and these birds generally carry moderate to large fat stores, some probably large enough for the full journey to just south of the desert. The short-distance migrants that are mainly due to winter in the Mediterranean region (like the Robin Erithacus rubecula) arrive later, around the beginning of October, and carry less fuel deposits. Mainly resident birds (like the Sardinian Warbler Sylvia melanocephala) do not build up any substantial fat reserves and their phenologies do not indicate much migratory movement.